PENGARUH CORPORATE GOVERNANCE TERHADAP PROFITABILITAS PERUSAHAAN - Islami, Nungky Wanodyatama (LP2M Institut Teknologi dan Bisnis Asia Malang, 2018)
This study aims to analyze the effect of corporate governance as measured by the variables of the board of commissioners, the proportion of independent members of the board of commissioners, the number of board of commissioners and audit committee meeting on the profitability of the company as measured by return on equity (ROE). The population used in this study is a manufacturing company listed on the Indonesia Stock Exchange during 2013-2016. Sampling technique used in this research is purposive sampling method and obtained 48 samples. This study uses secondary data from annual reports obtained from Indonesia Stock Exchange (BEI) in the period 2013-2016. The method of analysis used to analyze data is multiple regression. Based on the results of hypothesis testing in this study, it is evident that (1) the size of the board of commissioners has a positive effect on the profitability of the company. (2) the proportion of independent members of the board of commissioners positively affects the profitability of the company. (3) the board of commissioners meeting positively affect the profitability of the company. (4) audit committee negatively affect the profitability of the company.